Action Research Supporting Students' Oral Language in Northern Canadian Schools: A Professional Development Initiative - Shelley Stagg Peterson (Journal of Research in Rural Education, 2012)
Interview, document, and observational data were used to examine grade K-2 teachers' and literacy coaches' perceptions of the benefits and challenges of collaborative action research as a professional development initiative in rural schools. Eleven teachers and five literacy coaches in five northern Ontario school districts participated in collaborative action research supported by a university facilitator/researcher. Their goal was to enhance their teaching practices to support K-2 students' oral language development. The collaborative action research approach proved to be a relatively inexpensive and effective professional learning forum for the rural teachers, who had limited opportunities for formal professional development because of geographical distances between individual schools and major urban centers. The time commitment, often a challenge in action research, represented a particular constraint to rural teachers because of their heavy curricular responsibilities.